Juventude e gênero na Renovação Carismática Católica em Goiânia - Santos, Vanildes Gonçalves dos (2009)
This work aimed at investigating the Catholic church in Goiânia and its influence in young people life mainly in regards to the building of gender identities.The focus of the research is the Catholic Charismatic Movement ,named Catholic Charismatic Renewal RCC. The theoretical references to the studies were based on the social science framework which has been the basis for analysis and consideration concerning the Catholic Charismatic Religious Phenomenon in interface to the youth and gender. The field research was carried out in the city of Goiânia with young participants from RCC , specifically from the praying groups and the community of life. A qualitative research applying multimethods was used , e.g. individual and group interview and life story. The field research helped to identify how the youth building happens in RCC regarding to gender , it means , the formation upon representations and teaching of the Catholic Church Doctrine which paradigms support and legitimize male and female identities and roles socially built. The speech of the young people unveils how these teachings interfere in their lives and contribute to build their identity as women and men